A Study of Selected Flexi Cap Mutual Funds - Dr. Meghna Jain (Journal of Corporate Finance Management and Banking System ( JCFMBS) ISSN : 2799-1059, 2022)
This paper represents an overview on the performance evaluation of the flexi cap mutual funds. A mutual fund is a type of financial vehicle made up of a pool of money collected from many investors in order to invest in securities like stock, bonds, money market instruments and other assets. Flexi cap funds are open ended dynamic equity schemes that invest across large cap, mid cap and also small cap stocks. These funds allow the investors to diversify their portfolios across market capitalizations in order to reduce risk and volatility. Thus, the fund manager is responsible to analyze the potential of various businesses irrespective of their size and allocation of funds to different sectors and other businesses. This paper also attempts to analyze the best flexi cap mutual funds for the Generation Z. The objective of this research paper is to evaluate the performance of the Parag Parikh flexi cap fund, UTI flexi cap fund and PGIM India flexi fund over the time period of last four years i.e. 2018-19 to 2021-22.